Rent-sharing, hold-up, and wages: Evidence from matched panel data - David Card; Francesco Devicienti; Agata Maida (Institute for the Study of Labor (IZA), 2011)
It is widely believed that rent-sharing reduces the incentives for investment when long term contracts are infeasible because some of the returns to sunk capital are captured by workers. We propose a simple test for the degree of hold-up based on the fraction of capital costs that are deducted from the quasi-rent that determines negotiated wages. We implement the test using a data set that combines Social Security earnings records for workers in the Veneto region of Italy with detailed financial information for employers. We find strong evidence of rent-sharing, with an elasticity of wages with respect to current profitability of the firm of 3-7%, arising mainly from firms in concentrated industries. On the other hand we find little evidence that bargaining lowers the return on investment. Instead, firm-level bargaining appears to split the rents after deducting the full cost of capital.
urn:nbn:de:101:1-201111213134
Keywords: J31; 330; rent-sharing; hold-up; employer-employee data; Sunk Costs; Lohnpolitik; Produktivität; Arbeitsangebot; Arbeitsnachfrage; Matching; Betriebliche Investitionspolitik; Italien